(Agronomical and anatomical study of resulted early cocoa (Theobroma cacao L.) grafting - Adi Prawoto; Nurul Qomariyah; Sri Rahayu; Bambang Kusmanadhi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Cocoa grafting and budding is usually carried out on 4-5 month old seedling, thus it needs 9-12 months to be ready tranplanted to the field. Effort to shorten time in the nursery can be done by early propagation. The aim of this research was to study effect of clones, tying and foliar application of grafsticks on the percentage of graftake. This study was carried out in Kaliwining Experimental Station, 45 m a.s.l. and D climate type (Schmidt & Ferguson). First experiment was RCBD design and replicated 3 times, and factorial treatment 4 x 3. The first factor were clones, i.e. TSH 858, ICS 13, ICS 60 and DR 2, the second factor was grafstick wiring, i.e. without, wiring 2 and 4 weeks before using. The 2nd experiment using RCBD design replicated 3 times and factorial treatment 3 x 3 x 2. The first factor was clones, i.e. KW 162, KW 163 and KW 165; the second ones was wiring, i.e. without, wiring 2 and 4 weeks before using, and the 3rd factor was manuring, i.e. with and without foliar application. Rootstock was ICS 60 seedlings of 30 day old, and grafting method was cleft grafting above cotyledons. Variables observed include C and N total of the grafstick, percentage of graftake, shoot length, diameter, wet and dry weight. The result showed that because the grafstick flush periodically, graftstick wiring was not effective to increase total nutrient (C and N) on the grafstick. Furthermore, their effect on the graftake was not significant. Until 30 days first, percentage of graftake was 90-100%, but then decreased sharply to 30-60% depend on the clones. From the first experiment, DR 2 showed the highest graftake (62%), and KW 162 (39%) was the 2nd ones. Symptom on the death plants was started on the new leaves, that showed wilt, necrotic then fall. Isolation of those symptoms in the laboratory showed that Rhizoctonia solani, Phytophthora palmivora and Colletotrichum gloeosporioides. Anatomical analysis of the death graft union showed parenchymatous linked, weak and hollow when microtomised. Health union showed lignified accumulation that made tight union. It can be concluded that early cocoa grafting will success if the nursery is separated far from cocoa plantation, the medium is steril from soil borne disease, the graftstick is health, and tying of graft union must tight enough, then disease control must be done properly.Key Words : Theobroma cacao, clone, wiring, graft union, graftake.